The Effect of Family Social Support on Student Engagement in Online Learning - Ari Gusmawan; Sigit Hariyadi (Educational Guidance and Counseling Development Journal, 2022)
The Covid-19 pandemic has also strengthened the shift in learning activities in the educational environment which was originally carried out directly in schools to online which can be accessed anywhere. In addition to the covid 19 outbreak issue, this shift is also based on the development of communication technology that is very adequate. This shift in the way of learning is also felt by students at the elementary school level. A strong issue that arises in this shift in the way of learning is student engagement in participating in online learning. This engagement includes involvement in behavior, emotions, and thoughts. One of the factors that influence students in participating in online learning is the social support of their families. The purpose of the study was to analyze the effect of family social support on student engagement in participating in online learning at SDN Jejeruk, Blora Regency. The method used is correlational quantitative using a total sampling of all populations of 85 students. Data collection was carried out with a psychological scale of family social support and a psychological scale of student engagement. The results of this study show the influence of family social support in the form of emotional support, appreciation, instrumental and information on student engagement of 10.6% obtained from the results of the coefficient of determination test (R2).